PERBAIKAN MUTU PRODUK GENTENG MELALUI PERBAIKAN BAHAN BAKU (Studi Kasus Di Perusahaan Genteng UD.Tanah Mas Jepara) - Adi W, Purnawan; Purwanggono, Bambang; Shodikin, Ali (Diponegoro University, 2008)
By there is complaint from a part of customer of Jepara roof tile user this time, that is about the product ofless good Jepara roof tile, like the roof tile is mossy easily, fragile, leaky, low compressive strength or it isbroken when it is trampling, the case is back grounded by the raw material and technology are not advanceyet and also process of making roof tile is less perfect.By neglecting available process and technology, the writers try to improve the quality product of Jepara rooftile through the improvement of raw material. By adding the sand to the raw material with composition ofweight comparison 10:1, 5:1, 3:1 (clay : sand) and make an experiment directly by definite plasticity, dryand fire shrinkage, compressive strength, porosity and with analysis of variable cost calculation, so it can beconcluded that by adding sand to the raw material with weight comparison 5:1 (clay : sand), it is provenmost exactly in improve or increase the quality product of Jepara roof tile.